Peningkatan Produktivitas Melalui Downtime Reducing Pada Industri Food & Beverage di Kabupaten Tangerang - Mochamad Saefullah; Furtasan Ali Yusuf; Uli Wildan Nuryanto (MES Management Journal, 2024)
The aim of this research is to test and analyze the concept of downtime reducing in increasing company productivity carried out in the food and beverage industry in Tangerang Regency through the intervening variables reliability and efficiency. This research uses a quantitative approach with a causality descriptive design. The sample in this study was 257 respondents who were employees in the F&B industry in Tangerang Regency. The data analysis method consists of descriptive tests using the three box method, inferential tests using the SEM (Structural Equation Modeling) method with the help of SmartPLS software and significance testing or hypothesis testing. The test and analysis results show that all the hypotheses tested have a positive and significant effect, meaning that downtime reducing can be a concept that can be applied to F&B companies in Kab. Tangerang to increase company productivity through the intervening variables reliability and efficiency.